Burnout, depression, and suicidal ideation among physicians before and during COVID-19 and the contribution of perfectionism to physicians’ suicidal risk - Kleinhendler-Lustig, Dafna; Hamdan, Sami; Mendlovic, Joseph; Gvion, Yari (Frontiers in Psychiatry, 2023)
Objectives: There is limited data regarding the prevalence of suicidal risk among physicians during COVID-19, and the risk factors relating to it. Dominant risk factors for suicide among physicians are depression and burnout. Maladaptive perfectionism may also serve as a profound risk factor for suicidality among physicians and may aggravate symptoms of distress under the challenges of COVID-19. This study aims to evaluate current suicidal risk, suicidal ideation, depression, and burnout before and during COVID-19 among physicians in Israel, and to identify the best sets of correlates between perfectionism and burnout, depression and suicidal ideation, during these time periods.Methods: A sample of 246 Israeli physicians (160 before COVID-19 and 86 during COVID-19) completed online surveys assessing lifetime suicidal risk, suicidal ideation during the last year and current suicidal ideation, depression, burnout symptoms and maladaptive perfectionism.Results: More than one-fifth of the sample (21.9%) reported high suicidal risk (Lifetime suicidal behaviours). More than one-fourth (27.2%) reported suicidal ideation during the last 12 months; and 13.4% reported suicidal ideation during the last three months. In addition, more than one-third (34.6%) exhibited moderate-severe levels of depressive symptoms and more than a half of the sample reported burnout symptoms. Maladaptive perfectionism was positively correlated with current suicidal ideation, burnout, and depression. Moderated serial mediation analysis demonstrated indirect effect of perfectionism on suicidal ideation by its impact on burnout and depression only during COVID-19. Before COVID-19, physicians were more likely to experience depressive symptoms.Physicians in Israel are at increased risk for depression and suicidal ideation, regardless of the COVID-19 pandemic. Maladaptive perfectionism was 2 found to be a risk factor for burnout, depression, and suicidal ideation. During the first waves of the pandemic, physicians were less likely to experience depressive symptoms. However, among physicians who were characterized with high maladaptive perfectionism, depression served as a significant risk factor for suicidal ideation during the pandemic, which places these individuals at increased risk for suicidality. These results highlight the importance of implementing intervention programs among physicians to reduce suicidal risk and to better identify rigid perfectionism and depressive symptoms.